Carotid-cavernous fistula as an ophthalmic disease requiring interdisciplinary treatment - Luboń, Wojciech; Luboń, Małgorzata; Mrukwa-Kominek, Ewa (Klinika Oczna / Acta Ophthalmologica Polonica, 2024)
The aim of this article is to report a case of direct carotid-cavernous fistula (CCF) and to outline the diagnostic pathway and interdisciplinary approach to the treatment of this condition. A 78-year-old patient was hospitalized with a suspected ocular tumor. She reported proptosis in the right eye (RE) for the past three months and a decrease in visual acuity in the same eye for the past two months. During admission, she presented with decreased visual acuity in the RE and elevated IOP. In the RE, pulsating proptosis, conjunctival chemosis, and hyperemia were noted. Fundoscopy revealed detachment of the choroid in all quadrants and disseminated retinal hemorrhages. Ultrasound revealed a hypoechogenic space in the retrobulbar area. Doppler US showed dilated superior ophthalmic vein and increased arterialized vascular flow. Due to a strong suspicion of CCF, the patient was referred to the Department of Radiology for digital subtraction angiography (DSA). The examination confirmed the diagnosis, revealing right-sided direct CCF. Due to the small size of the fistula, radiologists and ophthalmologists deliberated on the optimal therapeutic approach. However, due to severe ophthalmic symptoms and the potential for sight loss, embolization of the CCF was scheduled. The procedure was performed in a standard manner. Postoperatively, the patient’s general condition deteriorated, and ischemic stroke was diagnosed. An ophthalmic examination was done one month after embolization. Visual acuity in the RE improved, and the IOP stabilized. Currently, the patient receives regular neurological care. Carotid-cavernous fistula is a rare condition, yet it can pose a threat to vision, which should not be ignored. The ophthalmologist is typically the first healthcare provider to encounter a patient exhibiting symptoms of the disease. Treatment decisions should be based on an interdisciplinary consensus and carefully considered, given the potential risk of complications associated with the procedure.